ABCB1 confers resistance to carboplatin by accumulating stem-like cells in the G2/M phase of the cell cycle in p53null ovarian cancer - Danbi Lee; Hyun-Seok Jeong; Sun-Young Hwang; Yu-Gyeong Lee; Youn-Jung Kang (Cell Death Discovery)
Abstract High-grade ovarian serous carcinoma, mostly bearing the various mutations in the TP53 gene, typically relapses within six months after first-line therapy due to chemoresistance, with a median overall survival of less than a year. However, the molecular mechanisms of action behind acquired drug resistance, particularly in relation to different TP53 mutation types, have not been fully elucidated. In this study, we demonstrated that acquired resistance to carboplatin in SKOV3 harboring a p53null mutation, but not in OVCAR3 with a p53R248Q, induces a significant portion of cells accumulated in the G2/M phase of the cell cycle, where cells highly expressed stemness marker with elevated proliferative capacity, which we believe was reversed by ABCB1 inhibition to the levels observed in non-resistant parental cells. ABCB1 suppression re-sensitized carboplatin-resistant cells to additional genotoxic stress and reduced their proliferative ability by recovering DNA repair activity and lowering stemness-like features, especially in the G2/M-distributed fraction. This suggests that high levels of stemness and attenuated DNA repair function exhibited in the G2/M-accumulated portion may be a key contributor of chemoresistance in patients with ovarian cancer bearing a p53null mutation, but not other types of mutations expressing p53. Furthermore, the inhibition of ΔNp73 resulted in the suppression of ABCB1, which consequently restricted cell growth in carboplatin-resistant SKOV3, suggesting that the ΔNp73 may act as an upstream regulator of the ABCB1. Notably, combinatorial treatment of carboplatin with the p53 reactivator, APR-246, proved effective in overcoming chemoresistance in OVCAR3 with the p53R248Q. Our findings suggest that the ΔNp73-ABCB1 axis is a promising molecular target for carboplatin-resistant ovarian cancers harboring p53null mutations, which we uncovered could be utilized to increase the efficacy of conventional anti-cancer therapies, to develop more efficient combinatorial therapeutic interventions directed toward overcoming the chemoresistance and improving the survival rates in patients with ovarian cancer.